The Effect of Applying KWL (Know, Want, Learn) Strategy on Reading Comprehension at Grade IX in SMP Swasta Cinta Rakyat 3 Pematangsiantar - Siahaan, Renita Clara; Herman, Herman; Munthe, Melda Veby Ristella (Lembaga Riset Mutiara Akbar, 2025)
This study examines the effect of applying the KWL (Know, Want, Learn) strategy on students’ reading comprehension at Grade IX of SMP Swasta Cinta Rakyat 3 Pematangsiantar during the 2024/2025 academic year. The research aimed to determine whether the KWL strategy could significantly improve students’ understanding of descriptive texts. Using a quasi-experimental design, the study involved two groups: an experimental group taught using the KWL strategy and a control group taught conventionally. Each class consisted of 31 students selected through purposive sampling. Data were collected through pre-tests and post-tests and analyzed using SPSS version 25.0, including descriptive statistics and an independent samples t-test. The results showed a significant improvement in the experimental group’s mean score (31.61 to 74.19) compared to the control group (39.03 to 69.68). The p-value of 0.000 (p < 0.05) indicated a significant difference between the two groups. It can be concluded that the KWL strategy effectively enhances students’ reading comprehension by activating prior knowledge, setting learning purposes, and promoting reflection. Teachers are encouraged to integrate this strategy into reading lessons to foster better comprehension and engagement.